How security impacts tourism to low-income countries - Merza, Stefan (2016)
The steadily increasing international tourism has grown to become one of the largest export categories in the world. In this paper I study the effect of security on international tourism flow from the G-7 countries to low-income countries. I use a gravity type approach for cross-sectional data, the year 2014, with 10 variables among them two security variables. My results suggest that no relationship exists between security and tourism flows. However, I am reluctant to draw any type of definite conclusion due to possible weaknesses in method. By highlighting the economic contribution of international tourism, I feel it is necessary to continue with similar studies at both global and regional levels.